Islamic Republic of Mauritania : Second Review Under the Staff Monitored Program and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Second Review Under the Staff Monitored Program (SMP) for Mauritania. Mauritania's performance since the beginning of 2006 has been fully satisfactory. All quantitative targets and structural benchmarks under the SMP that covered the first six months of 2006 were observed. Sound macroeconomic policies reined in inflation and contributed to the elimination of the parallel foreign exchange market premium. The proposed Poverty Reduction and Growth Facility (PRGF)-supported program will consolidate the progress achieved during the SMP toward macroeconomic stabilization.